Letter to Jane Tolmach from Ruth Ehrlich - Ruth Ehrlich:::::: (1968)
A letter from Ruth Ehrlich that informs Jane Tolmach that materials supporting a Women's Rights Program have been sent to Democratic Convention delegates and will be presented at upcoming platform hearings. She notes a scheduled presentation at a "Grass Roots" platform hearing in Los Angeles and hopes to present the program at both the Sacramento and Chicago platform committee hearings. Ehrlich asks for Tolmach's guidance and assistance in encouraging party leaders to support inclusion of a Women's Rights plank in the state and national Democratic platforms.